Dominasi Lapisan Otak BAP Pencemaran Nama Baik di Kepolisian Perspektif Semiotika Kritis serta Implikasi Microlearning-nya - Firmansyah, Erfi; Rafli, Zainal; Murthado, Fathiaty (Universitas Indraprasta PGRI, 2025)
This study examines the dominance of the brain layers of the reporter and the accused in the Investigation Report (BAP) of the defamation case at Polda Metro Jaya with a critical semiotic perspective, as well as its implications in the application of micro-learning for learning Indonesian at the Senior High School (SMA) level. The dominance of the three brain layers—reptile, limbic, and neocortex—influences the way the reporter and the accused construct the narrative in the BAP. A critical semiotic approach is used to understand how these brain responses are reflected in word choice, sentence structure, and communication patterns in the BAP text. The results of the study indicate that the dominance of the reptilian brain more often causes defensive reactions, while the limbic layer strengthens emotional expression. Neocortex dominance, on the other hand, encourages a more logical and rational argumentation structure. Based on the analysis of the two reporters and two accused, it can be seen that in the first case, the reporter is dominant in the reptilian brain layer, while the accused tends to be dominant in the mammalian brain layer. In the second case, the reporter tends to be dominant in the mammalian brain layer, while the accused tends to be dominant in the neocortex brain layer. This study also suggests the application of micro-learning in Indonesian language learning in high schools so that students can understand and identify the construction of meaning and psychological context in legal language. With this understanding, it is expected that students will have better critical literacy skills in analyzing texts with complex social contexts.